The administration of physical education, sport, and leisure programs - Tillman, Kenneth G.; McCue, Betty Foster; Esslinger, Arthur A.; Voltmer, Edward F. (Boston : Allyn and Bacon, 1996)
This book is about: Administrative and management concepts; management responsibilities; Program administration; ...
Keywords: Administration; Physical education and training; Physical education and training -- Administration